Autism Spectrum Disorder: Review Article (Medico Legal Update, 2020)
Autism is a lifelong neuro developmental condition. It is characterised by differences in behavior, socialinteraction, communication, special interests and sensory processing. These differences can present peopleon the autism spectrum with challenges in how they interact with their environment.Some people on the autism spectrum may behave in non-typical ways, often in response to the differentways in which they experience their environment. Such behaviors are generally a way to communicate theirfeelings or to adapt to a situation, or may result from their heightened sensitivity to a sound or somethingthey have seen or felt.The researchers suggest that genes and environment play important roles in the causing of ASD. A more recentstudy examined the cell structure, size, and shape of the brains of individuals with ASD, they demonstratedthat different brain regions showed these differences more profoundly than others. The amygdala is thereforeproposed to be one of several neural regions that are abnormal in autism, and may associated with otherneurodisorders. There are several types of ASD according to the development of disease. While there isno single best treatment for ASD. There are association between the child’s diet and severity or frequencyof symptomatology; especially vitamin D, calcium, potassium, pantothenic and choline may persist in asignificant percentage of patients. Types of playing are very successful and designing appropriate playopportunities for children with ASD need to be the primary concerns for educators, clinicians, and parents.